Modification effects of microsecond high current electron beam exposure on titanium VT22 alloy - Donets, S.Ye.; Klepikov, V.F.; Lytvynenko, V.V.; Prokhorenko, E.M.; Startsev, O.A.; Lonin, Yu.F.; Ponomarev, A.G.; Uvarov, V.T.; Starovoytov, R.I. (Вопросы атомной науки и техники, 2019)
Titanium VT22 alloy was irradiated in the TEMP-A accelerator with the high current electron beam with the energy of 350 keV, beam current of 2 kA, pulse length around 4 µs, and beam diameter of 45 mm. The irradiation was performed for three samples with 1 to 3 pulses separately. Numeric simulations of the temperature distributions in the targets were conducted using the thermoelastic ablation model. The microstructural and mechanical properties of the irradiated alloy were studied using microhardness testing, metallography and fractography analysis. Сплав титану ВТ22 опромінювався в прискорювачі TEMP-A сильнострумовим електронним пучком з енергією 350 кeВ, струмом пучка 2 кА, довжиною імпульсу близько 4 мкс і діаметром пучка 45 мм. Опромінення проводили для трьох зразків 1-3 імпульсами. Чисельне моделювання розподілів температур у мішенях проводилося з використанням моделі термопружної абляції. Досліджено мікроструктурні та механічні властивості опроміненого сплаву з використанням вимірювання мікротвердості, металографічного та фрактографічного аналізів. Титановый сплав ВТ22 облучен в ускорителе TEMP-A сильноточным электронным пучком с энергией 350 кэВ, током пучка 2 кА, длиной импульса около 4 мкс и диаметром пучка 45 мм. Облучение проводили для трех образцов 1-3 импульсами. Численное моделирование распределения температуры в мишенях проводилось с использованием модели термоупругой абляции. Микроструктурные и механические свойства облученного сплава были изучены с использованием измерения микротвердости, металлографического и фрактографического анализов.